Design formulation of rabbit feed based on palm kernel cake (PKC) and oil palm frond (OPF) - Zulfadhli, Mohd (2012)
Palm oil miling is a major industry in Malaysia. The total area under oil palm estates cover more than 2 million hectares.The industry,besides producing palm oil, also produces by-products such as palm kernel cake(PKC)and oil palm frond (OPF) which is usable as animal feed.Palm oil mills in Malaysia currently produces an annual quantity of 1.4 million tons of PKC.Moreover,OPF is one of the most abundant agricultural by-products in Malaysia.Almost all pruned fronds are discarded in the plantation,mainly for nutrient recycling and soil conservation.Rabbits are herbivores that feed by grazing on grass,straw and leafy weeds. In consequence, their diet contains large amounts of cellulose, which is hard to digest.The study focused on the suitability of PKC and OPF as a major source of crude protein,crude fiber and as well as minerals and vitamins in the formulation of rabbit feed.The nutritional compositions of these raw materials and a common animal feedstuffs, maize and soybean meal are analyzed using Near-Infrared Spectroscopy (NIRS). The results of crude protein (CP) content using NIRS analysis are 17.24 % in PKC, 0.00 % in OPF, 7.51 % in maize and 38.76 % in soybean meal.The result of crude fiber(CF)content in OPF is 32.99 %.These feed ingredients are then grinded and mixed on proper formulation using laboratory blender.Final product 1 analyzed using NIRS has 15.79 % crude protein(CP),8.75 % crude fiber (CF) and 20.70 % acid detergent fiber (ADF) which represents high digestibility.Gross energy(GE)value is 4005.18 kcal/kg which resulted in a comparable appetite of rabbit with a commercial rabbit pellet.Final product 1 is considered suitable as a supplementary rabbit feed.Final product 2 and final product 3 are used as a comparison.At 40 % total formulation of PKC and OPF in the rabbit feed,the environmental problem of biomass from oil palm industry is solved.